2018
DOI: 10.20517/2394-4722.2018.16
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular control of chromosomal instability and maintenance of intra-tumoral heterogeneity

Abstract: Aim: Current cancer treatments are challenged by the plasticity of cancer cells, largely influenced by chromosomal instability (CIN) leading to variations in karyotype known as tumor-specific aneuploidy, which in turn, leads to intratumor cellular heterogeneity (TH). Cells with certain chromosomal defects often survive treatment and the growthassociated states of TH persist in recurrent tumors. Modulation of the CIN rate seems to reside within the tumor itself.In an attempt to develop a therapy targeting cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Cells used in this study were validated to be free of mycoplasma by analyzing culture medium with MycoAlert PLUS Mycoplasma from Lonza and/or PCR‐based Venor GeM Mycoplasma Detection Kit (Sigma‐Aldrich). Identification of mutations in TP53 , PTEN , IDH1 , and IDH2 and DNA copy number variation of PTEN and EGFR were carried out using cDNA and DNA samples of GBM primary cultures, following PCR‐based mutation assay with sequencing and comparative quantitative PCR, respectively, as described previously . The genetic identity profiles of 16 short tandem repeats were determined based on DNA samples by IDEXX RADIL, with results shown in Table .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells used in this study were validated to be free of mycoplasma by analyzing culture medium with MycoAlert PLUS Mycoplasma from Lonza and/or PCR‐based Venor GeM Mycoplasma Detection Kit (Sigma‐Aldrich). Identification of mutations in TP53 , PTEN , IDH1 , and IDH2 and DNA copy number variation of PTEN and EGFR were carried out using cDNA and DNA samples of GBM primary cultures, following PCR‐based mutation assay with sequencing and comparative quantitative PCR, respectively, as described previously . The genetic identity profiles of 16 short tandem repeats were determined based on DNA samples by IDEXX RADIL, with results shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Human fibulin-3 variant (h-fibulin-3-v), a novel cancer therapeutic agent, has been developed in our laboratory after recognizing that its parental protein EFEMP1 has a role in cancer evolution with a cell context-dependent dual function. [2][3][4] Human fibulin-3 variant functions in the extracellular compartment through multifaceted tumor suppression mechanisms. As such, it would effectively inhibit tumor cells from reforming tumor mass, and would be less susceptible to therapeutic escape leading to recurrence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sansregret and colleagues show that one mechanism to restrain excessive CIN in tumor cells and increase fitness is through mutations in the anaphase promoting complex/cyclosome [160]. A recent study on cell cultures of glioblastoma multiforme showed that low cell-plating density caused increase of CIN rate, suggesting cancer cells' ability to sense cue from extracellular environment to alter their CIN rate [161]. Furthermore, they found that EGF-containing fibulin-like extracellular matrix protein 1 (EFEMP1, also known as fibulin-3) played an inhibitory function of CIN triggered by low cell-plating density in vitro and low cell inoculum volume in vivo [161,162].…”
Section: Cancer Therapeutic Development By Exploiting Chromosome Instmentioning
confidence: 99%
“…Understanding such “Yin and Yang” reciprocal aspects of CIN could facilitate development of future cancer therapeutic strategies, which could potentially prevent cancer recurrence and progression. Supporting this theory, Zhou et al showed extracellular control of CIN rate in glioblastoma cells, and further demonstrated that EFEMP1, which is a cell context-dependent extracellular matrix protein, functions as an inhibitor of CIN [ 161 ].…”
Section: Exploiting Cancer’s Evolutionary Tactics For Future Cancementioning
confidence: 99%